Gut microbiota and fecal metabolic signatures in rat models of disuse-induced osteoporosis - Qiao, Xiaochen; Zhang, Kun; Li, Xiaoyan; Lv, Zhi; Wei, Wenhao; Zhou, Ruhao; Yan, Lei; Pan, Yongchun; Yang, Sen; Sun, Xiaojuan; Li, Pengcui; Xu, Chaojian; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background Assessing the correlation between gut microbiota (GM) and bone homeostasis has increasingly attracted research interest. Meanwhile, GM dysbiosis has been found to be associated with abnormal bone metabolism. However, the function of GM in disuse-induced osteoporosis (DIO) remains poorly understood. In our research, we evaluated the characteristics of GM and fecal metabolomics to explore their potential correlations with DIO pathogenesis. Methods DIO rat models and controls (CON) underwent micro-CT, histological analyses, and three-point bending tests; subsequently, bone microstructures and strength were observed. ELISAs were applied for the measurement of the biochemical markers of bone turnover while GM abundance was observed using 16S rDNA sequencing. Metabolomic analyses were used to analyze alterations fecal metabolites. The potential correlations between GM, metabolites, and bone loss were then assessed. Results In the DIO group, the abundance of GM was significantly altered compared to that in the CON group. Moreover, DIO significantly altered fecal metabolites. More specifically, an abnormally active pathway associated with bile acid metabolism, as well as differential bacterial genera related to bone/tissue volume (BV/TV), were identified. Lithocholic acid, which is the main secondary bile acid produced by intestinal bacteria, was then found to have a relationship with multiple differential bacterial genera. Alterations in the intestinal flora and metabolites in feces, therefore, may be responsible for DIO-induced bone loss. Conclusions The results indicated that changes in the abundance of GM abundance and fecal metabolites were correlated with DIO-induced bone loss, which might provide new insights into the DIO pathogenesis. The detailed regulatory role of GM and metabolites in DIO-induced bone loss needs to be explored further.